2020
DOI: 10.15252/embj.2020104494
|View full text |Cite
|
Sign up to set email alerts
|

LRRK 2 activation controls the repair of damaged endomembranes in macrophages

Abstract: Cells respond to endolysosome damage by either repairing the damage or targeting damaged endolysosomes for degradation via lysophagy. However, the signals regulating the decision for repair or lysophagy are poorly characterised. Here, we show that the Parkinson's disease (PD)‐related kinase LRRK2 is activated in macrophages by pathogen‐ or sterile‐induced endomembrane damage. LRRK2 recruits the Rab GTPase Rab8A to damaged endolysosomes as well as the ESCRT‐III component CHMP4B, thereby favouring ESCRT‐mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
159
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 27 publications
8
159
0
Order By: Relevance
“…LLOMe treatment results in the recruitment of LRRK2 and its substrate Rab8A to damaged endolysosomes (12, 13). We therefore tested LRRK2 and Rab8A positive vesicle formation in response to endolysosomal damage in M-CSF and GM-CSF differentiated BMDM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LLOMe treatment results in the recruitment of LRRK2 and its substrate Rab8A to damaged endolysosomes (12, 13). We therefore tested LRRK2 and Rab8A positive vesicle formation in response to endolysosomal damage in M-CSF and GM-CSF differentiated BMDM.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages have taken centre stage in the quest to identify immune functions of LRRK2, particularly because resident macrophages in form of microglia can be found in the brain. We have recently shown that endomembrane damage in macrophages constitutes a trigger for LRRK2 activation resulting in Rab GTPase phosphorylation and ESCRT-mediated membrane repair (12). Here, we demonstrate that macrophage differentiation modulates the ability of macrophages to activate LRRK2 and the kind of response that is mounted to endomembrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…Both coordinate the activity of the ESCRT-III complex for membrane repair. In contrast, depletion of LRKK2 and Rab8A change the damage response phenotype from membrane repair to lysophagy [ 134 ].…”
Section: Membrane Damage Recognition and Cell Responsementioning
confidence: 99%
“…Mutations in several genes encoding for lysosomal proteins are involved in Parkinson's disease (PD). In this issue, Herbst et al (2020) show that PD-related leucinerich repeat kinase 2 (LRRK2) is activated in response to pathogen or membranolytic drug-induced damage of phagolysosomes and lysosomes in macrophages, and regulates endolysosomal homeostasis by controlling the balance between membrane repair and degradation.…”
mentioning
confidence: 99%
“…These findings raised the question of what recruits the ESCRT machinery to the site of the damage. In their paper, Herbst and colleagues elegantly address this and reveal that, in macrophages, LRRK2 recruits the small GTPase Rab8A and CHMP4B to damaged endolysosomes, thereby controlling the decision between membrane repair and lysophagy (Fig 1) (Herbst et al, 2020). LRRK2 is a multidomain protein kinase that phosphorylates various members of the Rab GTPase family.…”
mentioning
confidence: 99%